How Enterprise Digital Transformation Reshapes Risk Sharing between Banks and Enterprises: Based on Multiperiod DID Analysis - He, Xingyuan; Li, Tianxin; Wang, Lin (Transformations In Business & Economics, 2026)
The digital transformation of enterprises is seen as a key variable in reshaping bank–enterprise relationships and enhancing a financial system’s resilience. However, the literature has rarely provided a systematic explanatory framework or theoretical mechanisms for how and whether it alters the risk-taking behavior between banks and enterprises. Drawing on theories of information asymmetry and financing constraints, using the data from nonfinancial listed companies on China’s A-share market from 2013 to 2021, a multiperiod difference-in-differences model was employed to explore how corporate risk-taking influences bank risk-taking, and the heterogeneous effects were examined based on enterprises’ level of digital transformation, R&D investment, and information transparency. Results reveal that corporate risk-taking has a significant inhibiting effect on bank risk-taking, exhibiting a clear inverse change. Furthermore, the results after incorporating the effects of digital transformation reveal that corporate risk-taking has a significant promoting effect on bank risk-taking, leading to a clear positive change. In particular, corporate risk-taking influences bank risk-taking through the mechanisms of information asymmetry and financing constraints, serving as a mediating effect. The degree of competition between enterprises also plays a significant positive moderating role between corporate and bank risk-taking, thereby enhancing the promoting effect of corporate risk-taking on bank risk-taking. Furthermore, the influence of corporate risk-taking on bank risk-taking is heterogeneous, and enterprises with higher digital transformation levels, more R&D investment, and better information transparency have a more pronounced positive promoting effect. The conclusions provide decision-making support for the coordinated promotion of bank–enterprise risk-sharing through digital transformation.